The Hybrid Multiple-Criteria Decision-Making Model for Home Healthcare Nurses' Job Satisfaction Evaluation and Improvement - YanJiao Wang; YanJiao Wang; YaQin Ye; Yanjun Jin; Yen-Ching Chuang; Yen-Ching Chuang; Ching-Wen Chien; Tao-Hsin Tung (Frontiers Media S.A., 2022)
Objectives: To investigate and evaluate the key factors related to job satisfaction performance of home healthcare nurses (HHNs).Methods: A total of 31 HHNs from three community hospitals in Zhejiang province were invited to participate in the study. They completed a questionnaire survey based on the home healthcare nurse job satisfaction scale (HHNJS) from February to March 2022. Consistent fuzzy preference relation (CFPR) methods and important-performance analysis (IPA) were used to obtain the attribute weights and performance for HHNs job satisfaction.Results: The results showed that the attributes of C13, C14, C15, C23, C24, C42, C51, and C52 were key factors influencing HHNs job satisfaction.Conclusion: The hybrid multiple-criteria decision-making (MCDM) model can help home-healthcare-agency administrators better understand the key factors related to HHNs job satisfaction and establish reasonable improvement strategies.